2019
DOI: 10.1038/s41416-019-0638-8
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of 3-hydroxybutyrate dehydrogenase type 2 promotes proliferation and metastasis of nasopharyngeal carcinoma by iron retention

Abstract: BACKGROUND: 3-Hydroxybutyrate dehydrogenase type 2 (BDH2) is known to catalyse a rate-limiting step in the biogenesis of the mammalian siderophore and regulate intracellular iron metabolism. Here we aim to explore the expression and possible function of BDH2 in nasopharyngeal carcinoma (NPC). METHODS: The transcription and protein expression of BDH2 in NPC were determined by both real-time RT-PCR and immunohistochemistry staining assays. Cell proliferation, migration and invasion were evaluated by MTT assay, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…The conversion process between Fe 3+ and Fe 2+ is accompanied by the generation of energy, which benefits cellular energy metabolism ( 49 ). Similarly, it was demonstrated that reducing the level of intracellular iron via the tumor suppressor gene 3-hydroxybutyrate dehydrogenase type 2 inhibited the proliferation and metastasis of NPC cells ( 50 ). Furthermore, Xu et al ( 51 ) indicated that itraconazole was able to reduce the activity of NPC stem cells by increasing the concentration of intracellular iron in lysosomes and lipid peroxides.…”
Section: Targeting Ferroptosis To Sensitize Npc To Rtmentioning
confidence: 99%
“…The conversion process between Fe 3+ and Fe 2+ is accompanied by the generation of energy, which benefits cellular energy metabolism ( 49 ). Similarly, it was demonstrated that reducing the level of intracellular iron via the tumor suppressor gene 3-hydroxybutyrate dehydrogenase type 2 inhibited the proliferation and metastasis of NPC cells ( 50 ). Furthermore, Xu et al ( 51 ) indicated that itraconazole was able to reduce the activity of NPC stem cells by increasing the concentration of intracellular iron in lysosomes and lipid peroxides.…”
Section: Targeting Ferroptosis To Sensitize Npc To Rtmentioning
confidence: 99%
“…Transferrin and transferrin receptors, which enable iron internalization from the extracellular environment, are necessary for ferroptosis (98,102). A low level of BDH2 (3-hydroxybutyrate dehydrogenase 2) amplifies NPC cell malignant behaviours by promoting intracellular iron overload, indicating that reduced intracellular iron might be favourable for NPC treatment (103). Fe is a S-adenosylmethionine (SAM) to provide methyl groups, and the formation of SAM depends on extracellular folic acid, which can be increased in NPC cells by a-folate receptor activity (108).…”
Section: Fe Metabolismmentioning
confidence: 99%
“…Not all metabolic changes have to be increased to have a major effect on tumour biology. For example, it is shown in the study by Li et al 12 that low expression of 3-hydroxybutyrate dehydrogenase type 2 (BDH2) has a major effect on tumour iron metabolism in nasopharyngeal carcinoma. Apart from its effect on ketone body metabolism, BDH2 also affects intracellular iron concentrations, responds to iron and helps in the synthesis of a siderophore.…”
Section: Novel Pathwaysmentioning
confidence: 99%